Efficacy of Ectrin® (Fenvalerate) for sarcoptic mange control in swine - E L Wooten; A B Broce; D S Pollmann (Kansas Agricultural Experiment Station Research Reports, 1984)
A trial was conducted to determine the efficacy of fenvalerate (EctrinÂ®) for control of sarcoptic mange mites in swine. Artificially infested pigs were treated with two sprayings of Ectrin at 0.05% concentration with 1 wk interval between sprayings. One week after the first spraying, mite numbers and clinical signs of mange had decreased in treated animals but remained elevated in infested-nontreated pigs. Four weeks after the first spraying (3 wk after the second spraying), no mites were found in scrapings from the Ectrin-treated pigs and the amount of scratching and rubbing in those pigs decreased compared with the infested- nontreated pigs. It was concluded that Ectrin is an effective control for sarcoptic mange in pigs at the 0.05% level when two sprayings are used.; Swine Day, Manhattan, KS, November 15, 1984
Keywords: Swine day; 1984; Kansas Agricultural Experiment Station contribution; no. 85-132-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 461; Swine; Ectrin; Sarcoptic mange; Efficacy